The Effectiveness of Health Education to Increasing Hemoglobin Levels in Pregnant Women as Stunting Prevention Effort - Fitri, Aida; Fajri, Nova; Darmawati, Darmawati (Media Karya Kesehatan, 2024)
Stunting is a nutritional health problem that is the center of attention worldwide with cases reaching 150.8 million people (22.2%). Stunting causes failure of growth and development of toddlers which has an impact on increasing mortality, morbidity, physical and cognitive disorders in adolescence and adulthood. Mothers who are malnourished during pregnancy are prone to anemia. Mothers with anemia can give birth to children who are at risk of stunting. This study aims to see the effectiveness of health education on increasing hemoglobin in pregnant women to prevent stunting. This research method was quasi-experimental with one group pre-post test. Sampling was done by purposive sampling method. The number of samples in this study was 60 samples. The data were analyzed using a normality test, and then a different test was performed using Wilcoxon. This study was conducted from August-September 2020. The results showed the effectiveness of health education during pregnancy in increasing the Hb value in pregnant women as indicated by the difference in the average Hb concentration before the intervention and after the intervention with a value of sig. (0.00) < (0.05). It was expected that health workers in primary health care facilities and hospitals provide continuous education to pregnant women in fulfilling balanced nutrition and consuming at least 90 iron tablets during pregnancy to prevent stunting.Keywords: Health education, hemoglobin, pregnant women, stunting.